THE EFFECT OF MAGNET LENGTH AND WIDTH ON FLUX LINKAGE IN A 12S8P PERMANENT MAGNET SYNCHRONOUS GENERATOR - Setiawati, Yuli; Prasetyono, Rizki Noor; Munawar, Aris (Journal of Electronic and Electrical Power Applications, 2025)
Permanent Magnet Synchronous Generator 12S8P as an energy conversion tool. To increase the efficiency of electrical energy, it is necessary to design a generator using FEM software to simulate the length and width of the magnet, so that when making the generator it can achieve a high level of success. Experimental quantitative method by varying the length and width then analyzing how much influence it has on the flux linkage. The results of the influence of the length of the magnet and the width of the magnet on the resulting flux linkage, the calculated f value = 14.979 with a significance or probability level of 0.001 <0.05 which can be concluded that the data is acceptable and shows that variations in length and width (20 x 5 mm) have an effect on the flux linkage. In addition to the ANOVA results, the results of the summary model also show a large coefficient of determination of 0.591, which means that variations in length and width (20 x 5 mm) have an influence of 59.1% on the flux linkage, with the remaining 40.9% influenced by other factors. Meanwhile, in the variation of Length and Width (30 x 10 mm), the ANOVA results were obtained with a calculated f value = 18.979 with a significance or probability level of 0.001 <0.05, which can be concluded that the data can be accepted and the variation of Length and Width (30 x 10 mm) has an effect on flux linkage. In addition to the ANOVA results, the summary model results also showed a determination coefficient of 0.429, which means that variations in Length and Width (30 x 10 mm) have an influence of 42.9% on flux linkage, with the remaining 57.1% influenced by other factors.